The Differential Influence of Identification on Ethical Judgment: The Role of Brand Love - Dalman, M. Deniz (Journal of business ethics, 2019)
As negative information about companies becomes widely available and spreads rapidly through digital communications, understanding consumer reactions to these events and how human perceptions are shaped becomes increasingly important. In this paper, we investigate how consumers’ identification with brands and their love for them affect their support for the brand during extremely unethical (negative) situations. The results indicate that brand identification both decreases (direct effect) and increases (indirect effect through brand love) consumers’ ethical judgment following extremely unethical events. Moreover, we find that consumers who are in a love type relationship with the brand proactively shield the brand from other consumers by employing two brand supportive behaviors; sin of omission and brand defense.